„Das kannst du einem anderen weismachen!“. Ein Kommentar zu „Die Antiquiertheit des Hassens“ von Günther Anders - Maomed Parraguez, María Carolina (Scenari, 2021)
The monstrous acts that are nowadays committed in the name of everything possible and that use a sophisticated technical development (such as nuclear technology, for example) are facts without people: we neither fight against people nor are we fought by people, explains Anders. Hatred cannot be behind a massacre, not even behind the specter of a massacre - its only possibility - since controversy, murder and elimination take place as a special moment in a process with broader goals. Its engine will undoubtedly not be evil either, for it is a goal of itself. These inhuman, calculated and foreseen actions are in the best case only an "enterprise", which in turn will have its evaluation and in the realization of which the person, immersed in deep alienation, intervenes.